Tell it on the mountain : the daughter of Jephthah in Judges 11 - Miller, Barbara, 1942- (Collegeville, Minn. : Liturgical Press, 2005)
"A consideration of Jephthah's daughter in Judges 11-12:7, using feminist and midrashic interpretations"--Provided by publisher.
Beginning the conversation -- Rabbinic midrash as a conversation partner -- Feminist critique as a conversation partner -- The rabbis speak -- The feminists speak -- The rabbis and feminists converse about values -- Modern midrash--an ongoing dialogue.
"A Michael Glazier book."
Includes bibliographical references and index.
Keywords: Jephthah's daughter -- (Biblical figure); Bible. -- Criticism, interpretation, etc., Jewish; Bible. -- Feminist criticism; Midrash